PHYTOCHEMICAL SCREENING AND COMPARATIVE BRINE SHRIMP CYTOTOXICITY EVALUATION OF ETHANOLIC CRUDE EXTRACT AND FRACTIONS OF Parquetina nigrescens LEAVE - Adebayo, K. O; Isah, Y; M. E, Khan (FUDMA Journal of Sciences, 2025)
Parquetina nigrescens is extensively used in African traditional medicine, yet a systematic, solvent-polarity-guided evaluation of its cytotoxic potential is lacking. This study aimed to validate its ethnomedicinal use by investigating the phytochemical constituents and cytotoxic activity of its extracts, with a focus on how solvent polarity influences bioactivity. Methods: The P. nigrescens leaves was exhaustively extracted with absolute ethanol then sequentially fractionated using solvents of increasing polarity (n-hexane, chloroform, ethyl acetate, n-butanol, and water). Phytochemical profiling was conducted via standard qualitative methods, and cytotoxicity was evaluated using the Brine Shrimp Lethality Assay (BSLA). Results: Phytochemical screening confirmed a rich profile of alkaloids, flavonoids, and triterpenoids in the plant. The BSLA revealed that all extracts demonstrated significant cytotoxicity (LC₅₀ < 1000 µg/mL). Most importantly, a statistically significant difference in potency was observed across the fractions (p < 0.0001), revealing a critical solvent-polarity dependency. The butanol and aqueous fractions exhibited superior and remarkably similar potency (LC₅₀ = 70 and 72 µg/mL, respectively), significantly more cytotoxic than the mid-polar ethyl acetate (142 µg/mL) and non-polar fractions (n-hexane: 366 µg/mL; chloroform: 555 µg/mL). The crude ethanol extract was the least potent (LC₅₀ = 660 µg/mL) obviously due to the masking effect of other compounds in the matrix. Conclusion: This study provides robust evidence that the cytotoxic potential of P. nigrescens is significantly influenced by solvent polarity (p < 0.0001). The high potency of the butanol and aqueous fractions validates the plant’s traditional use in water-based preparations.